RETRACTED: Rapid assessment of soil contamination in case of a technogenic emergency situation - Kalach A.V.; Elfimov N.V.; Sagirov E.A.; Nefedov S.A.; Ageev P.M. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001